Development of the South Pacific Vulnerable Marine Ecosystem bioregionalisation - Bennion, Matthew; Rowden, Ashley A.; Moore, Bradley R.; Anderson, Owen F.; Tablada, Jordi; Geange, Shane W.; Stephenson, Fabrice (Frontiers in Ecology and Evolution, 2025)
IntroductionVulnerable Marine Ecosystems (VMEs) are characterized by species that are at heightened risk of destruction or removal by bottom fishing. In the high seas, Regional Fisheries Management Organizations (RFMOs) are required to implement measures to prevent Significant Adverse Impacts (SAIs) on VMEs. Impact assessments are routinely conducted to inform said measures. The spatial scale at which impact assessments are conducted has a considerable impact on results obtained, and therefore on management actions taken. Bioregions can provide an ecologically relevant scale for impact assessments; therefore, the aim of this study was to develop a VME-specific bioregionalization to inform management of SAIs on VMEs.MethodsOccurrence records of VME indicator taxa and spatially explicit environmental variables were compiled. Gradient forest models were applied to estimate taxon compositional turnover, and a hierarchical classification approach was used to generate groups. Statistical approaches and visual assessment were used to inform the appropriate number of groups to represent VME bioregions.ResultsA 7-group VME-specific bioregionalization for the western part of the South Pacific Ocean is presented and described in detail including summary statistics and descriptions of the environmental conditions which characterize each bioregion. Two distinct spatial estimates of uncertainty are provided for use in spatial planning. Average bioregion area was 635,428 km2 (range: 6,111 to 1,913,667 km2), with the largest, Bioregion 5, accounting for 43% of the study area.DiscussionThe bioregionalization presented offers an opportunity to conduct impact assessments at an ecologically relevant scale, with specific reference to VMEs. While this approach was developed to help inform management of VMEs in the South Pacific, the approach used could be applied for the spatial management of biodiversity in other areas beyond national jurisdiction.